Efeitos do treinamento no perfil oxidativo-inflamatório de mulheres com síndrome metabólica - Steckling, Flávia Mariel (2015)
The modification of sedentary patterns added to sedentarism are strictly related to the increase in obesity and the onset of metabolic syndrome (MS). Obesity sets a causal relation with many diseases, including insulin resistance, cardiovascular disease, type II diabetes and a systemic inflammatory state common to such diseases. MS is closely associated with chronic low-grade inflammation and oxidative stress. The index of women in post menopause with MS is growing, according to studies, since they are susceptible to oxidative stress frame. Although the regular practice of regular physical exercise is indicated as one of the best non-pharmacological interventions for the prevention and treatment of MS, few studies have examined the effects of high-intensity interval training HIIT - isolated on oxidative, inflammatory, and anthropometric parameters for functional postmenopausal in women with MS, not concurrently it is not found in literature a period of detraining in the same population. The intervention consisted of three weekly sessions of HIIT protocol on treadmills, and the prescribed training intensity was individualized and controlled by heart monitors. The training consisted of 12 weeks and two weeks of detraining, with an effective increased estimating the maximum oxygen consumption after training, but after two weeks of detraining, it was observed a significant reduction. The following training protocol levels of nitrite and nitrate (NOx) increased and remained in the detraining period, as well as advanced products of protein oxidation (advanced oxidation protein products - AOPP). After twelve weeks of HIIT, it was not observed weight loss. Although we found significant improvement in the inflammatory profile, interleukin-1 beta levels (IL-1β), interleukin- 6 (IL-6), tumor necrosis factor alpha (TNF-α), interferon-gamma (IFN-γ) showed significant reduction after this period and returned to significant levels after the two weeks of detraining. HIIT also proved to be effective in increasing the levels of interleukin-10 (IL-10) and subsequently to two weeks of detraining partially reversed this benefit. Thus, it is concluded that this HIIT protocol was not sufficient to reduce oxidative stress, although the benefits of the inflammatory profile of this population given by the regular practice of high-intensity aerobic exercise are independent of weight loss.